PENERAPAN RESTORATIVE JUCTICE DALAM PERKARA KEKERASAN DALAM RUMAH TANGGA DI KEJAKSAAN NEGERI BIREUEN - Mutia, Salsabilla; Bahreisy, Budi; Saputra, Ferdy (Fakultas Hukum Universitas Malikussaleh, 2023)
This study aims to examine the application of restorative justice in domestic violence cases at the Bireuen District Prosecutor's Office. This research uses qualitative research with an empirical juridical approach. Based on the results of the research, it is that the efforts made by the Prosecutor's Office in implementing mediation follow the Attorney General's regulations Number 15 of 2020 in article 5 paragraph 1 concerning Termination of Prosecutors Based on Restorative Justice which is carried out for 14 days from the time the letter is submitted by the investigator to the Prosecutor's Office. There is also an obstacle that occurs during the mediation settlement process, namely the difficulty of uniting the opinions of the victim and the perpetrator in order to reach a mutual agreement. Furthermore, the pattern of mediation carried out by the Bireuen District Prosecutor's Office is mediation in court in accordance with the JAMPIDUM circular (Junior Attorney General for General Crimes) starting from RJ.1 to RJ.16.Keywords: Restorative Justice, Violence, Domestic.